Testacella Haliotidea (Draparnaud) Free Living in Pennsylvania - Branley A. Branson (Hello World!, 1976)
On 9 October 1975, Dr. C. J. McCoy, Jr., Carnegie Institute, Pittsburgh, Pennsylvania, collected one adult specimen of this slug from the concrete steps of the museum. Although the species has been reported from a Pennsylvania greenhouse (Dundee, 1974), this is the first record from a metropolitan out-of-doors site. Additional North American localities include Illinois, Nova Scotia greenhouses, and Tennessee (Dundee, 1974), San Francisco, California and Oregon (Hanna, 1966).